Effect Of Maltodextrin Concentration On Physicochemical Properties And Level Of Instant Drink Liked Powder Fruit (Ananas comosus L. merr) - Christine F. Mamuaja; Siti Mutia Ifriani Tueno; Thelma D. J. Tuju (Sam Ratulangi University, 2022)
This research on pineapple powder instant drink processing aims to determine the effect of variations in maltodextrin concentration on the physicochemical properties and level of preference of pineapple fruit powder instant drink (Ananas comosus L.merr). Pineapple is a perishable food, so its shelf life is relatively short. One of the processing to extend the shelf life of the product is to use it as a raw material in the manufacture of powdered instant drinks. Powdered instant drink is a food product in the form of fine grains, practical in serving, easily soluble in hot or cold water. In the manufacture of instant powdered drinks, a filler material is needed, one of which is maltodextrin, which functions to prevent damage to the material due to heat, as well as increase its solubility. The results showed that the addition of 15% maltodextrin was the treatment with the least amount of damage to vitamin C with vitamin C content of 108.27 mg/100gr, total soluble solids 94.67 Â°brix, soluble time 13.27 seconds, preference for taste 5.56. , aroma 4.6, and color 5.08.Keywords: Drink powder, Pineapple, Maltodextrin